Prevention of isoniazid toxicity by NAT2 genotyping in Senegalese tuberculosis patients. (2016) - Toure, A.; Cabral, M.; Niang, A.; Diop, C.; Garat, A.; Humbert, L.; Fall, M.; Diouf, A.; Broly, F.; Lhermitte, M.; Allorge, D.
Abstract: Isoniazid (INH), recommended by WHO (World Health Organization) in the treatment of tuberculosis (TB), is metabolized primarily by the genetically polymorphic N -acetyltransferase 2 (NAT2) enzyme. The human population is divided into three different phenotypic groups according to acetylation rate: slow, intermediate, and fast acetylators. The objective of this study was to explore the relationship between NAT2 genotypes and the serum concentrations of INH. Blood samples from 96 patients with TB were taken for the analysis. NAT2 polymorphisms on coding region were examined by polymerase chain reaction (PCR) direct sequencing; the acetylation status was obtained by measuring isoniazid (INH) and its metabolite, acetylisoniazid (AcINH) in plasma was obtained by using the liquid chromatography coupled to mass spectrometry. TB patients were distributed into two groups of fast and slow acetylators according to the acetylation index calculated based on the plasma concentration of INH in the 3rd hour (T3) after an oral dose. Our PCR analysis identified several alleles, where NAT2*4, NAT2*5A, NAT2*6A, and NAT2*13A were the most important. The concentrations of INH varied between 1.10 mg/L and 13.10 mg/L at the 3rd hour and between 0.1 and 9.5 mg/L at the 6th hour. The use of the acetylating index I3 allowed the classification of tested patients into two phenotypic groups: slow acetylators (44.3% of TB patients), and rapid acetylators (55.7%). Patient's acetylation profile provides valuable information on their therapeutic, pharmacological, and toxicological responses.